Observances: psychology, public security policies and incarcerated youth - Holsbach Hadler, Oriana; Maria de Fátima Guareschi, Neuza; Cristina Coelho Scisleski, Andrea (Revista Pesquisas e Práticas Psicossociais, 2019)
This article aims to discuss the production of an expertise between psychology and security, specially regarding ways of observing and intervening towards the young subject considered dangerous. Based on Michel Foucault’s studies, this analysis focuses on the relation between those fields of knowledge questioning the observance strategies engendered by psychological practices within public security policies. In these terms, the article brings quotidian scenes based on ethnographical experiences from within a project entitled ‘Imprisoned Youth Observatory’ located inside the Central Prison of Porto Alegre (Rio Grande do Sul, Brazil) that make it possible to question the way psychological knowledge produces young people in conflict with the law. Through this analysis, it is possible not only to visualize how psychology privatizes a domain over the incarcerated young offender, but also how this science creates dead-end destinies to this youth who are considered a ‘social problem’. Keywords: Psychology; Prison; Youth; Public Security Policies